A tin dioxide quantum dot, a preparation method and application thereof

CN122877797APending Publication Date: 2026-10-09GUANGZHOU HONGWU MATERIAL TECH CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202611077936.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-20
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

[0006]现有二氧化锡量子点的制备方法大多需引入油酸、油胺等大分子有机配体调控晶粒尺寸,后续配体热解去除不彻底易残留绝缘组分,同时普遍存在工艺流程复杂、制备成本偏高的问题

Benefits of technology

1、本发明采用溶胶-凝胶法结合水热法制备二氧化锡量子点,方法简便,能够合成平均粒径约53Å、结晶性优良的四方相金红石型二氧化锡量子点,颗粒尺寸均匀且具备典型的量子尺寸效应。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122877797A_ABST
    Figure CN122877797A_ABST
Patent Text Reader

Abstract

The application relates to the technical field of semiconductor materials, in particular to a tin dioxide quantum dot and a preparation method and application thereof. The preparation method comprises the following steps: dissolving tin tetrachloride pentahydrate in deionized water, adding ammonia water drop by drop until precipitation is completed, and performing dialysis treatment on the precipitation to obtain a purified tin precursor precipitation; dispersing the tin precursor precipitation in deionized water, adjusting the pH to 11-12, and performing a hydrothermal reaction, so that tin dioxide quantum dots are obtained after drying. The tin dioxide quantum dots are prepared by adopting a sol-gel method combined with a hydrothermal method, the method is simple, tetragonal rutile type tin dioxide quantum dots with an average particle size of about 53 angstroms and excellent crystallinity can be synthesized, the particle size is uniform, and the tin dioxide quantum dots have typical quantum size effects; and the tin dioxide quantum dots can be used for preparing a tin dioxide quantum dot film, a tin dioxide gas-sensitive material or a perovskite solar cell.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of semiconductor materials technology, specifically to a tin dioxide quantum dot, its preparation method, and its application. Background Technology

[0002] Tin dioxide (SOD) is a typical n-type wide-bandgap semiconductor material. With its excellent chemical stability, tunable morphology, and outstanding photoelectrochemical properties, it holds core application value in two major fields: electron transport layers for perovskite solar cells and resistive gas sensors. In the optoelectronic field, the wide bandgap and high electron mobility of SOD quantum dots due to quantum size effects have made them a key electron transport material for improving the efficiency and long-term stability of perovskite solar cells. In the gas sensing field, SOD exhibits intrinsically high catalytic activity towards reducing gases such as ethanol, making it the most widely used commercially available metal oxide gas-sensitive substrate material.

[0003] Currently, the preparation of tin dioxide quantum dots generally relies on organic ligands such as oleic acid, oleylamine, or macromolecular polymers to control particle size. These intrinsically insulating organic coatings, remaining inside the material, significantly increase charge transport and gas mass transfer impedance, requiring high-temperature calcination above 400°C for removal. This not only drastically increases preparation energy consumption but also makes it unsuitable for low-temperature processing scenarios such as flexible substrates and inverted perovskite solar cells. Furthermore, most existing tin dioxide quantum dot aqueous dispersion systems are acidic media, easily corroding the perovskite light-absorbing layer, making direct application to inverted structure devices difficult. Chinese invention patent application CN118851252A discloses a method for preparing monodisperse nano-tin dioxide quantum dots in aqueous solution, using stannate as a raw material. After precipitation with a weak organic acid and hydrothermal reaction, quaternary ammonium salt and dimethyl sulfoxide are added to achieve aqueous dispersion of the quantum dots. However, this method introduces organic solvents such as dimethyl sulfoxide, lacks a deep impurity removal step in the pretreatment, makes it difficult to ensure no organic residue after low-temperature annealing, and does not simultaneously optimize performance in both photoelectric transmission and gas sensing fields.

[0004] Meanwhile, existing tin dioxide-based gas sensors generally rely on high-temperature operating conditions above 300°C, resulting in insufficient response sensitivity at low temperatures. The high specific surface area and surface defect advantages of quantum dot materials have not been fully utilized in the gas sensing field. Therefore, developing a tin dioxide quantum dot preparation technology that is simple to process, environmentally friendly, produces no residue after low-temperature annealing, and is suitable for both optoelectronic and gas sensing applications has significant industrial value and research significance. Summary of the Invention

[0005] The first aspect of the present invention provides a method for preparing tin dioxide quantum dots, comprising the following steps: dissolving tin tetrachloride pentahydrate in deionized water, adding ammonia dropwise until precipitation is complete, dialyzing the precipitate to obtain a purified tin precursor precipitate; dispersing the tin precursor precipitate in deionized water, adjusting the pH to 11-12, carrying out a hydrothermal reaction, and drying to obtain tin dioxide quantum dots.

[0006] Most existing methods for preparing tin dioxide quantum dots require the introduction of macromolecular organic ligands such as oleic acid and oleylamine to control the grain size. Subsequent ligand pyrolysis removal is often incomplete and leaves residual insulating components. In addition, these methods generally suffer from complex processes and high preparation costs. This invention employs a sol-gel method combined with a hydrothermal method to prepare tin dioxide quantum dots. First, tin tetrachloride pentahydrate is used as a precursor, which undergoes a hydrolysis reaction via ammonia titration to generate tin hydroxide sol precipitate. This precipitate is then purified by dialysis to thoroughly remove impurities such as chloride ions, preventing residual impurities from degrading the crystal quality and photoelectric properties of the material. Subsequently, the precursor dispersion is adjusted to a strongly alkaline environment (pH 11-12) under hydrothermal conditions, where the tin hydroxide precursor undergoes dehydration condensation and Ostwald ripening crystallization, gradually transforming into tetragonal rutile tin dioxide crystals with complete crystalline phases. By precisely matching the hydrothermal temperature, holding time, and system alkalinity, the grain growth scale can be controlled within the quantum size range. Finally, tin dioxide quantum dots with an average particle size of approximately 53 Å, excellent crystallinity, and uniform particle size are synthesized, exhibiting typical quantum size effects. Furthermore, the overall preparation process is simple, requires no complex organic ligand modification, and is both economical and scalable.

[0007] The hydrothermal reaction is carried out at a temperature of 180-220℃ for 7-12 hours.

[0008] A second aspect of the present invention provides tin dioxide quantum dots, wherein the average particle size of the tin dioxide quantum dots is 30-80 Å.

[0009] The third aspect of this invention provides an application of tin dioxide quantum dots for the preparation of tin dioxide quantum dot films, tin dioxide gas-sensitive materials, or perovskite solar cells.

[0010] The method for preparing the tin dioxide quantum dot film includes the following steps: dispersing the tin dioxide quantum dots in deionized water containing tetraethylammonium hydroxide to obtain a tin dioxide quantum dot colloid; spin-coating the tin dioxide quantum dot colloid onto the surface of a substrate and annealing it to obtain a tin dioxide quantum dot film.

[0011] The substrate surface has undergone ultraviolet dust removal treatment.

[0012] The tin dioxide quantum dot colloid contains 1-15 wt% tin dioxide quantum dots.

[0013] Optionally, the content of tin dioxide quantum dots in the tin dioxide quantum dot colloid is 1-9 wt%.

[0014] The content of tetraethylammonium hydroxide in each mL of colloid is 2.5-250 μL.

[0015] Optionally, the content of tetraethylammonium hydroxide per mL of colloid is 2.5-20 μL.

[0016] The raw materials for preparing the tin dioxide gas-sensitive material include a ceramic tube substrate, a gold electrode, a heating wire, and a gas-sensitive layer, wherein the gas-sensitive layer comprises tin dioxide quantum dots.

[0017] Beneficial effects 1. This invention uses a combination of sol-gel method and hydrothermal method to prepare tin dioxide quantum dots. The method is simple and can synthesize tetragonal rutile tin dioxide quantum dots with an average particle size of about 53 Å and excellent crystallinity. The particles are uniform in size and have typical quantum size effects.

[0018] 2. This invention uses tetraethylammonium hydroxide to disperse tin dioxide quantum dots, which can construct a quantum dot colloidal system with excellent dispersibility in alkaline water medium. After the film is annealed at a low temperature of 150°C, the tetraethylammonium hydroxide is completely decomposed without organic residue, thus avoiding interference of organic matter with the photoelectric properties of the film.

[0019] 3. The tin dioxide quantum dots of the present invention can be used to prepare quantum dot films. By limiting the content of tin dioxide quantum dots in the tin dioxide quantum dot colloid to 1-15wt%, the film sample has the strongest transient light response, high electron transfer rate and high carrier concentration. At the same time, it exhibits a significant optical anti-reflection effect in the visible light band, with the highest transmittance reaching 116% (relative to the blank substrate).

[0020] 4. The present invention performs ultraviolet dust removal treatment on the substrate surface, reduces the contact angle between tin dioxide quantum dot colloid and the substrate, improves the wettability of the dispersion on the substrate surface, and improves the film quality.

[0021] 5. The tin dioxide quantum dots prepared by this invention can be used to prepare resistive gas-sensitive elements. Under the test conditions of 200℃ working temperature and 50ppm ethanol gas, the element response value Ra / Rg can reach 8.0, and it has fast desorption kinetics and good cycle reversibility. Attached Figure Description

[0022] Figure 1 The image shows the XRD pattern of tin dioxide quantum dot powder from Example 1.

[0023] Figure 2 The particle size of tin dioxide quantum dot powder in Example 1 was calculated using MDIjade software based on the XRD pattern.

[0024] Figure 3 The images shown are SEM and TEM images and electron diffraction patterns of the product of Example 1, where (a) and (b) are SEM images of tin dioxide quantum dot powder at magnifications of 100,000 and 150,000, respectively; (c), (d) and (e) are TEM images of tin dioxide quantum dot colloids at sizes of 5 nm, 10 nm and 20 nm; and (f) is an electron diffraction pattern of a selected individual crystallite in the tin dioxide quantum dot powder.

[0025] Figure 4 This is a SEM image of the tin dioxide quantum dot film from Example 1.

[0026] Figure 5 The XPS spectra of the tin dioxide quantum dot film in Example 1 are shown in (a) XPS full spectrum; (b) Sn3d high-resolution spectrum; (c) O1s high-resolution spectrum; (d) Sn3d fine spectrum; and (e) O1s fine spectrum.

[0027] Figure 6 The contact angle test results of the tin dioxide quantum dot colloids prepared in Examples 1-6 on the ITO conductive surface without UV dust removal are shown in (a)-(f), which correspond to Examples 2, 3, 1, 4, 5 and 6 respectively.

[0028] Figure 7 The contact angle test diagram of the tin dioxide quantum dot colloid prepared in Example 1 on the conductive surface of ITO under ultraviolet dust removal conditions.

[0029] Figure 8 This is a test diagram of the contact angle between anhydrous ethanol and the conductive surface of ITO under conditions without UV dust removal.

[0030] Figure 9 The following are the quantum dot colloidal dispersion test diagrams for Examples 1 and 7-11: (a) Colloidal dispersion diagram, where from left to right are the control group, Example 7, Example 1, Example 8, Example 9, Example 10, and Example 11; (b) Particle size distribution histogram, where 0 μL, 10 μL, 20 μL, 40 μL, 60 μL, 80 μL, and 1000 μL correspond to the control group, Example 7, Example 1, Example 8, Example 9, Example 10, and Example 11, respectively.

[0031] Figure 10The following are the photoelectric performance test results of the tin dioxide quantum dot films prepared in Examples 1-5: (a) CV curve; (b) transmission spectrum; (c) short-circuit photocurrent curve; (d) open-circuit photovoltage curve; (e) LSV curve; (f) Mott-Schottky curve and fitted line; where void is the blank sample (uncoated ITO conductive glass) as the control group, and 1.0%, 1.5%, 3.0%, 6.0%, and 9.0% correspond to Examples 2, 3, 1, 4, and 5, respectively; the instrument used for testing is an electrochemical workstation, the solvent is deionized water, and the inert electrolyte is Na2SO4. Electrolytes K3[Fe(CN)6] and K4Fe(CN)6·3H2O need to be added in (a) and (f).

[0032] Figure 11 This is a physical image of the gas-sensitive element prepared in Example 12.

[0033] Figure 12 This is a circuit diagram for a static gas testing method.

[0034] Figure 13 The transient response-recovery curve of the gas-sensitive element prepared in Example 12 to 50 ppm ethanol gas at an operating temperature of 200°C is shown. Detailed Implementation

[0035] Example 1 A method for preparing tin dioxide quantum dots includes the following steps: dissolving 7g of SnCl₄·5H₂O in deionized water, titrating with 2mol / L ammonia, and repeatedly washing the Cl₂ using a dialysis bag. - The process continued until no flocculent precipitate was formed upon titration with 0.05 mol / L AgNO3 solution. The treated product was dispersed in deionized water, and ammonia was added to adjust the pH to between 11 and 12. The product was then placed in an autoclave (hydrothermal treatment conditions: 200℃, 9h). After hydrothermal treatment, the product was evaporated and dried in a drying oven at 120℃ to obtain tin dioxide quantum dot powder.

[0036] An application of tin dioxide quantum dots is disclosed for the preparation of tin dioxide quantum dot thin films. The preparation method of the tin dioxide quantum dot thin film includes the following steps: dispersing the tin dioxide quantum dots in deionized water containing tetraethylammonium hydroxide to obtain a tin dioxide quantum dot colloid; spin-coating the tin dioxide quantum dot colloid (500 rpm at low speed and 4000 rpm at high speed) onto ITO (indium tin oxide) glass, and then annealing it at 150°C for 1 hour on a hot stage to obtain a tin dioxide quantum dot thin film.

[0037] The tin dioxide quantum dot colloid contains 3 wt% tin dioxide quantum dots; the content of tetraethylammonium hydroxide per mL of colloid is 5 μL.

[0038] Example 2 The specific implementation method is the same as in Example 1; the difference is that the content of tin dioxide quantum dots in the tin dioxide quantum dot colloid is 1 wt%.

[0039] Example 3 The specific implementation method is the same as in Example 1; the difference is that the content of tin dioxide quantum dots in the tin dioxide quantum dot colloid is 1.5 wt%.

[0040] Example 4 The specific implementation method is the same as in Example 1; the difference is that the content of tin dioxide quantum dots in the tin dioxide quantum dot colloid is 6 wt%.

[0041] Example 5 The specific implementation method is the same as in Example 1; the difference is that the content of tin dioxide quantum dots in the tin dioxide quantum dot colloid is 9 wt%.

[0042] Example 6 The specific implementation method is the same as in Example 1; the difference is that the content of tin dioxide quantum dots in the tin dioxide quantum dot colloid is 15wt%.

[0043] Example 7 The specific implementation method is the same as in Example 1; the difference is that the content of tetraethylammonium hydroxide in each mL of colloid is 2.5 μL.

[0044] Example 8 The specific implementation method is the same as in Example 1; the difference is that the content of tetraethylammonium hydroxide in each mL of colloid is 10 μL.

[0045] Example 9 The specific implementation method is the same as in Example 1; the difference is that the content of tetraethylammonium hydroxide in each mL of colloid is 15 μL.

[0046] Example 10 The specific implementation method is the same as in Example 1; the difference is that the content of tetraethylammonium hydroxide in each mL of colloid is 20 μL.

[0047] Example 11 The specific implementation method is the same as in Example 1; the difference is that the content of tetraethylammonium hydroxide in each mL of colloid is 250 μL.

[0048] Example 12 A method for preparing tin dioxide quantum dots is the same as in Example 1.

[0049] An application of tin dioxide quantum dots in the fabrication of a gas-sensitive element is disclosed. The fabrication method comprises the following steps: 5 mg of tin dioxide quantum dot powder is added to a centrifuge tube and mixed with 1 drop of deionized water, then ultrasonically treated for 5 min to prepare a uniformly dispersed slurry; the dispersed slurry is uniformly coated onto a ceramic tube with two gold electrodes and four wires using a dropper, and dried in an oven at 60°C for 30 min to form a uniform gas-sensing film on the ceramic tube; the ceramic tube is welded to a specially designed 6-legged base, and a nickel-chromium alloy heating wire is inserted into the center of the ceramic tube as a heat source; the tube is aged at the operating temperature for 24 h to obtain the desired gas-sensitive element. Figure 11 The gas-sensitive element shown.

[0050] Performance testing methods and data 1. The tin dioxide quantum dot powder prepared in Example 1 was subjected to XRD testing.

[0051] Figure 1 It can be seen that the diffraction peaks in the XRD pattern are consistent with the standard PDF card of tin dioxide (JCPDS (41-1445)). Figure 1 (a) The structure below is consistent with the tetragonal rutile structure. The (110) plane, (101) plane and (211) plane are the three major characteristic peaks, among which the (110) plane is the strongest peak. The above can prove that its material composition is tin dioxide with a tetragonal crystal structure.

[0052] like Figure 2 As shown, the average particle size was calculated to be 53 Å with an error of ±1 Å using MDIjade software, indicating that the tin dioxide prepared by the above method is a quantum dot and the particle size is uniform.

[0053] 2. The tin dioxide quantum dot powder, tin dioxide quantum dot colloid, and tin dioxide quantum dot film prepared in Example 1 were subjected to SEM and TEM tests.

[0054] Figure 3 This is a SEM image of a tin dioxide quantum dot powder sample. Figure 3 (a) and Figure 3 (b) are images of the powder sample magnified to 100,000x and 150,000x respectively. The images show that the size of the tin dioxide quantum dots is about 10nm, which is larger than the XRD calculation result. This indicates that the quantum dots may have agglomerated after the prepared tin dioxide quantum dot aqueous solution was dried.

[0055] Figure 4 This is a scanning electron microscope image of a tin dioxide quantum dot film sample magnified 150,000 times. As can be seen from the image, the quantum dots are uniformly covered on the ITO film and the particle size is uniform, which is consistent with the SEM data of the powder.

[0056] Figure 3(c)- Figure 3 (e) are TEM images of tin dioxide quantum dot colloids at different magnifications. Figure 3 (f) is Figure 3 (c) An image obtained by performing FFT processing on a single grain. Figure 3 As shown in (c), the quantum dots are approximately 5 nm in size and have a spindle-shaped shape. Through observation... Figure 3 (c) It can be seen that the tin dioxide quantum dots obtained by this preparation process have good crystallinity and distinct grain boundaries. Good crystallinity indicates that the tin dioxide quantum dot crystals prepared by this process have a low defect state density. A low defect state density can reduce electron capture and recombination when tin dioxide quantum dots are used as ETL devices, which is beneficial for improving the electron mobility of the device and thus improving PCE. Since the grain boundaries are rich in oxygen vacancies and dangling bonds, the distinct grain boundaries indicate that the surface of the tin dioxide quantum dots has a large number of gas adsorption active sites. Through further analysis... Figure 3 (c) Measure and label the interplanar spacing. Figure 3 (f) The crystal planes corresponding to the diffraction rings show that the crystal plane data are consistent with the XRD results.

[0057] 3. The tin dioxide quantum dot film prepared in Example 1 was subjected to XPS analysis.

[0058] Figure 5 (a) is the XPS full spectrum, with each characteristic peak labeled. The results show that the elements present after annealing of tin dioxide quantum dots in film formation are Sn, O, Cl, and C. The C peak is caused by unavoidable carbon contamination and is located near 285 eV. Elements present in tetraethylammonium hydroxide do not appear in the full spectrum, indicating that tetraethylammonium hydroxide decomposes during annealing and may disappear in the form of gas or vapor. Therefore, there is no residual tetraethylammonium hydroxide in the chemical composition of the film, which avoids interference with the film performance. In addition, it can be found that the Cl peak is much smaller than the O and Sn peaks and can be basically ignored, indicating that the removal of Cl- is very thorough in this process. Figure 5 (b)-(c) show the high-resolution spectra of Sn. The binding energies of the 3d orbital electrons corresponding to the two peaks are 486.5 eV and 494.9 eV, respectively. Looking up the table, these energy levels are within the binding energy range of Sn⁴⁺, indicating that the Sn valence state in the thin film sample is +4. The results of peak separation of the Sn and O peaks are as follows... Figure 5 As shown in (d)-(e). Figure 5 The two peaks in (d) exactly cover the two peaks of Sn, indicating that Sn in the thin film sample... 4+ The Sn element constitutes the majority of the Sn element in the thin film sample. Figure 5(e) shows the O fraction, with binding energies at 530.55 eV and 531.04 eV, respectively. The 530.55 eV peak corresponds precisely to the lattice oxygen of tin dioxide, exhibiting a relatively high intensity, indicating that the quantum dot maintains a well-preserved crystalline framework. The 531.04 eV peak is due to oxygen vacancies and surface hydroxyl groups, suggesting that the quantum dot surface is rich in defect sites. This provides a very wide conductivity modulation space for the adsorption and redox reactions of the target gas.

[0059] 4. Wetting analysis of tin dioxide quantum dot colloids of different concentrations (Examples 1-6) on ITO conductive surfaces.

[0060] Take 30 μL of the tin dioxide quantum dot colloid from Examples 1-6, and drop it onto ITO conductive surfaces that have and have not undergone UV dust removal, respectively, and measure the contact angle. Figure 6 As shown in Table 1, with increasing concentration, the sample with the best wettability was 3.0%, with a contact angle of 56.44°. When the concentration exceeded 3.0%, the contact angle between the sample and the ITO conductive surface increased with further concentration. After UV dust removal treatment of the ITO conductive glass, the contact angles of all samples decreased, as shown in Table 1. Figure 7 As shown. This is because UV dust removal reduces the surface energy of the conductive surface-air interface and the conductive surface-liquid interface. When anhydrous ethanol is dropped onto a thin film sample that has not undergone UV dust removal, it almost completely spreads into an extremely thin water film on the surface. The contact angle is then measured. Figure 8 As shown, the contact angle is less than 10°, indicating a superhydrophilic state. This is because the quantum dot surface has a large number of exposed hydroxyl groups and defects, resulting in excellent wettability of organic matter with hydrophilic groups or water on this surface. This indicates that the quantum dot surface has a large number of active sites that are highly sensitive to ethanol molecules, consistent with XPS data.

[0061] Table 1

[0062] 5. Dispersion test The tin dioxide quantum dot colloids prepared in Examples 1 and 7-11 were used for dispersibility testing, with no tetraethylammonium hydroxide added as a control group. Figure 9 As shown, without the addition of tetraethylammonium hydroxide, the system exhibits poor dispersibility and the liquid is quite turbid. Adding tetraethylammonium hydroxide improves the dispersibility; at a concentration of 5 μL / ml, the quantum dots are completely dispersed in the system. Further increases in the tetraethylammonium hydroxide concentration do not result in any noticeable change in the dispersion. The particle size distribution of the seven samples was tested, and the particle size distribution histograms are shown below. Figure 9As shown, without the addition of tetraethylammonium hydroxide, nearly 40% of the particles have a diameter greater than 40 nm. When the addition amount is greater than 0 and less than 20 μL, most of the particles have a diameter below 5 nm. When the addition amount is greater than 20 μL, the particle size begins to increase. This is because tetraethylammonium hydroxide is a strong base, and its strong alkalinity acts as a catalyst during synthesis or modification. It promotes the dehydration condensation reaction between unreacted tin precursors or residual -OH groups on the surface of the original quantum dots. This base-catalyzed condensation reaction promotes further growth of the inorganic framework or cross-linking of the grains, thus leading to an increase in particle size. Given that an addition amount of 10 μL is insufficient to completely disperse the quantum dots, 20 μL is the optimal addition amount.

[0063] 6. Photoelectric performance testing The tin dioxide quantum dot films prepared in Examples 1-5 were tested. like Figure 10 As shown in (a), the difference between the redox peaks in the CV curves of Examples 1-5 is much smaller than that in the control group, which proves that the film of the present invention has excellent compactness.

[0064] like Figure 10 As shown in (b), there is a significant anti-reflection phenomenon in the short-wavelength region, with the 9.0% thin film sample achieving a transmittance of 116%. However, the 9.0% thin film sample exhibits the lowest transmittance in the long-wavelength region, particularly in the wavelength range greater than 850 nm, and also in the region with wavelengths less than 400 nm. This indicates that it has the strongest light absorption capacity in both the long and short wavelength bands. This is because the thin film acts as an optical anti-reflection coating, reducing specular reflection at the glass / ITO interface, allowing more photons to penetrate the ETL and enter the core perovskite light-absorbing layer. The more photons that enter, the more photogenerated charge carriers are generated, thereby significantly increasing the short-circuit current density of the battery.

[0065] The photovoltage of five samples was tested. Initially, the samples were in a darkened state. After 20 seconds, a cycle of 20 seconds of illumination followed by 20 seconds of no illumination was established. The results are as follows: Figure 10 As shown in (d), the results indicate that among the five samples, the highest change in open-circuit photovoltage with increasing concentration occurred in the 9.0% sample. When illumination is off, the photovoltage exhibits a gradual relaxation process. In transient photovoltage (TPV) theory, the rate of photovoltage decay directly reflects the speed of nonradiative recombination. An appropriate relaxation curve implies that the quantum dot film can effectively passivate interface traps and slow down the reverse recombination of photogenerated electrons and holes. This is crucial for improving the open-circuit voltage of perovskite solar cells and can greatly alleviate the hysteresis effect caused by interface charge accumulation.

[0066] The photocurrent was tested, and the results are as follows: Figure 10As shown in (c), the results indicate that among the five sets of photocurrent curves, the sample with the highest photocurrent was 9.0% when subjected to 20s of continuous 1.5 times simulated sunlight irradiation. Furthermore, after being exposed to shading and then re-irradiated, the photocurrent change was the largest. This demonstrates that after quantum dot film deposition, it not only provides an extremely high photogenerated carrier collection rate but also has very few internal trapped states, allowing for rapid and unimpeded electron injection. The extremely rapid establishment and high saturation value of this transient photocurrent prove that the quantum dot film can extract and conduct photogenerated electrons generated in the perovskite layer to the ITO electrode at an extremely high speed under illumination. This directly corresponds to the intrinsically high short-circuit current density Jsc and excellent quantum efficiency (IQE / EQE) of the perovskite solar cell.

[0067] To further investigate the photoelectrochemical transport dynamics of quantum dot thin films, linear sweep voltammetry (LSV) tests were performed under illumination. Figure 10 As shown in (e), all samples exhibit typical n-type semiconductor photoelectric response characteristics in the negative bias range. Each component shows a distinct current-on inflection point near -0.5V to -0.4V, which is highly consistent with the flat-band potential (Efb) derived from the Mott-Schottky curve, indicating that the applied bias effectively overcomes the interface barrier and suppresses nonradiative recombination of photogenerated carriers. Among all samples, the 9.0% concentration component exhibits the largest photoelectric polarization current and the steepest slope under high negative bias, quantitatively confirming its superior bulk conductivity and charge extraction rate.

[0068] To quantitatively elucidate the energy level structure and intrinsic electrochemical properties of tin dioxide quantum dot films, Mott-Schottky (MS) measurements were performed. Figure 10 As shown in (f), within the depletion region, the 1 / C2-V curves of all samples exhibit a standard positive slope linear characteristic, confirming that the prepared quantum dot films are typical n-type semiconductors.

[0069] Analyzing the flat-band potential, we can use the following linear fitting formula:

[0070] In the formula, εn is the relative permittivity, ε is the vacuum permittivity, and N is the donor (for n-type semiconductors) or acceptor (for p-type semiconductors) concentration; E and Efb are the electrode potential and flat-band potential, respectively, both relative to a specific reference electrode. Based on the above equation, a linear fit is performed on the part of the curve with the fastest slope change in the Mott-Schottky plot. The intercept of the extended line on the potential axis is the value of Efb; N can be obtained from the slope of the line. Further extrapolation from the horizontal intercept of the Mott-Schottky curve shows that the flat-band potentials Efb of the 1.0%, 1.5%, 3.0%, 6.0%, and 9.0% concentration components are distributed around -0.45V and -0.40V, respectively. With the increase of spin-coated colloid concentration, Efb shows a slight positive shift trend, mainly attributed to the weakening of the quantum confinement effect caused by the close packing of nanoparticles during high-concentration film formation, and the slight downward shift of the Fermi level caused by grain boundary modulation. Next, we examined the carrier concentration N: based on the slope of the linear region, the donor carrier concentration of quantum dot films with different concentrations was quantitatively calculated. As shown in Table 2, the carrier concentration N for all samples was 10. 20 -10 21 cm -3 This is on the order of magnitude, mainly due to the abundant intrinsic defects of oxygen vacancies on the surface of quantum dots, which provide a large number of donor electrons.

[0071] Table 2

[0072] 7. Test the performance of the gas-sensitive material prepared in Example 12. The static gas testing method uses the Zhengzhou Weisheng WS-30B gas-sensitive element testing system. This system mainly consists of a gas chamber, a gas-sensitive tester, and a data acquisition system. The test circuit diagram is shown below. Figure 12 As shown in the figure. The gas sensor is placed in an 18L gas chamber and connected to a gas-sensitive testing instrument for testing. The testing circuit of the instrument is shown in the figure. By changing the heating voltage V... h Determine the sensor's operating temperature. The sensor and the load resistor R in the circuit. l The total voltage applied to the test circuit in series is V. c By measuring the voltage V1 across the load resistor R1, the sensor resistance can be calculated and output to a computer. The concentration of the test gas in the gas chamber is controlled using a static gas mixing method: a certain amount of liquid gas V... OC Inject the gas into the heating stage in the gas chamber using a microsyringe. Turn on the heating control switch. The heat from the heating stage causes gas V to... OC The gas is rapidly vaporized, and the fan in the gas chamber is briefly turned on to ensure uniform mixing and form a test gas with a certain concentration. After the sensor response reaches its maximum, the gas chamber is opened to restore the test environment to clean air.

[0073] The calculation formula is as follows:

[0074] Where R s The resistance of the gas sensor is V. out The measured output voltage across the load resistor R1.

[0075] For ethanol sensitivity testing, the gas-sensitive element's sensitivity to ethanol was tested using the above-described test method. The element's operating temperature was 200℃, and the transient response-recovery curve was obtained at an ethanol gas concentration of 50ppm. (See attached image.) Figure 13 As shown, the device exhibits typical resistance sensing characteristics of an n-type oxide semiconductor. Without the target gas introduced, the device maintains excellent baseline resistance stability Ra in an air-based environment. Upon instantaneous injection of 50 ppm ethanol gas at 50 s, the device's response value Ra / Rg shows a rapid, explosive increase, jumping to 6.0 in a very short time. Subsequently, due to the gradual equilibrium of chemisorption and mass transfer diffusion of gas molecules deep within the porous slurry framework, the sensitivity reaches a peak plateau at 280 s, with a maximum response value as high as 8.0. This significant drop in resistance demonstrates the extremely high chemical reactivity of its surface. When pure air is reintroduced at 290 s, the device sensitivity experiences a sudden, precipitous drop due to the desorption of ethanol molecules and the removal of dissociation products. In the initial stage of air introduction, the response value drops sharply from 8.0 to 2.2 within seconds, exhibiting extremely excellent instantaneous desorption kinetics. Subsequently, the recovery curve shows a gentle tail-end two-stage kinetic characteristic, with the baseline eventually almost completely recovering to the initial equilibrium state of 1.2, demonstrating good reversibility.

Claims

1. A method for preparing tin dioxide quantum dots, characterized in that, The process includes the following steps: dissolving tin tetrachloride pentahydrate in deionized water, adding ammonia dropwise until precipitation is complete, dialysis of the precipitate to obtain a purified tin precursor precipitate; dispersing the tin precursor precipitate in deionized water, adjusting the pH to 11-12, carrying out a hydrothermal reaction, and drying to obtain tin dioxide quantum dots.

2. The preparation method according to claim 1, characterized in that, The hydrothermal reaction is carried out at a temperature of 180-220℃ for 7-12 hours.

3. A tin dioxide quantum dot prepared by the method according to claim 1, characterized in that, The tin dioxide quantum dots have a tetragonal rutile structure and an average particle size of 30-80 Å.

4. An application of the tin dioxide quantum dots according to claim 3, characterized in that, Used in the preparation of tin dioxide quantum dot films, tin dioxide gas-sensitive materials, or perovskite solar cells.

5. The application of tin dioxide quantum dots according to claim 4, characterized in that, The method for preparing the tin dioxide quantum dot film includes the following steps: dispersing the tin dioxide quantum dots in deionized water containing tetraethylammonium hydroxide to obtain a tin dioxide quantum dot colloid; spin-coating the tin dioxide quantum dot colloid onto the surface of a substrate and annealing it to obtain a tin dioxide quantum dot film.

6. The application of tin dioxide quantum dots according to claim 5, characterized in that, The tin dioxide quantum dot colloid contains 1-15 wt% tin dioxide quantum dots.

7. The application of tin dioxide quantum dots according to claim 6, characterized in that, The tin dioxide quantum dot colloid contains 1-9 wt% tin dioxide quantum dots.

8. The application of tin dioxide quantum dots according to claim 5, characterized in that, The content of tetraethylammonium hydroxide in each mL of colloid is 2.5-250 μL.

9. The application of tin dioxide quantum dots according to claim 8, characterized in that, The content of tetraethylammonium hydroxide in each mL of colloid is 2.5-20 μL.

10. The application of tin dioxide quantum dots according to claim 5, characterized in that, The raw materials for preparing the tin dioxide gas-sensitive material include a ceramic tube substrate, a gold electrode, a heating wire, and a gas-sensitive layer, wherein the gas-sensitive layer comprises tin dioxide quantum dots.

Citation Information

Patent Citations

  • Nanometer tin dioxide quantum dot monodispersed in aqueous solution and preparation method of nanometer tin dioxide quantum dot

    CN118851252A